The role of agrarian legislation in national security ensuring of the Republic of Belarus - Kuzmich, Iryna P. (Journal of the Belarusian State University. Law, 2024)
The author of the article analyses the norms of agrarian legislation in the sphere of veterinary and phytosanitary security taking into account the content of the new National security concept of the Republic of Belarus. The study raises the problem of the lack of terminological unity in terms of legislative consolidation of such concepts as veterinary and phytosanitary security, draws attention to the need to introduce a comprehensive risk-oriented approach in the implementation of veterinary and phytosanitary measures, emphasises the importance of implementing in practice the principle of transparency and access to information on the epizootic and phytosanitary condition of the country’s territory as an important guarantee in the system of ensuring national security.
Keywords: agrarian legislation; biological security; veterinary security; veterinary activity; quarantine and plant protection; national security; agriculture; phytosanitary security